Análise da eficiência em regiões industriais incentivadas: o caso do Polo Industrial de Manaus (PIM) - Morais, Raimundo Nonato de Souza (2019)
This paper estimates the efficiency and productivity measures with the objective to analyze which factors determine the technical inefficiency in industrial sectors, located in a region stimulated with the offer of fiscal incentives. The specific case is the Industrial Pole of Manaus (PIM) represented by its main 9 industrial subsectors, responsible for about 96% of sales. The data are from the performance indicators report of SUFRAMA, from 1994 to 2016 and from IPEADATA. The two-stage DEA technique with the Tobit model and the Malmquist Index comprised efficiency and productivity estimation methods and the determination of inefficiency factors. The main result is that the PIM operates with inefficiencies with a trend of increasing efficiencies, fueled by technical change, captured by the Malmquist Productivity Index. The exchange rate volatility and the tax incentive concession in the Tobit model are determinant factors of inefficiencies.